Surface Modification And Functionalization By Electrical Discharge Coating: A Comprehensive Review - Liew, Pay Jun; Yap, Ching Yee; Wang, Jingsi; Zhou, Tianfeng; Yan, Jiwang (IOP Publishing Ltd, 2020)
Hard coatings are extensively required in industry for protecting mechanical/structural parts that withstand extremely high temperature, stress, chemical corrosion, and other hostile environments. Electrical discharge coating (EDC) is an emerging surface modification technology to produce such hard coatings by using electrical discharges to coat a layer of material on workpiece surface to modify and enhance the surface characteristics or create new surface functions. This paper presents a comprehensive overview of EDC technologies for various materials, and summarises the types and key parameters of EDC processes as well as the characteristics of resulting coatings. It provides a systematic summary of the fundamentals and key features of the EDC processes, as well as its applications and future trends